Evaluation of Long-Time Decoction-Detoxicated Hei-Shun-Pian (Processed Aconitum carmichaeli Debeaux Lateral Root With Peel) for Its Acute Toxicity and Therapeutic Effect on Mono-Iodoacetate Induced Osteoarthritis - Zhang, Lei; Li, Ting; Wang, Rongrong; Xu, Jiaan; Zhou, Li; Yan, Li; Hu, Zhengyan; Li, Hongwen; Liu, Fucun; Du, Wenxi; Tong, Peijian; Wu, Huiling; et al. (Frontiers in Pharmacology, 2020)
Background: As a degenerative joint disease, osteoarthritis (OA) has no satisfactory therapy to date. In traditional Chinese medicine (TCM), Aconitum carmichaeli derived Hei-shun-pian (Hsp) has been developed for joint pain treatment. However, it causes adverse events in patients. Long-time decoction has been traditionally applied to reduce the aconite toxicity of aconite herbs, but its detoxifying effect is uncertain. Methods: Hsp was extracted with dilute decoction times (30, 60 and 120 min) and evaluated by toxicological, chemical, pharmacological assays. Acute toxicity assay and chemical analysis were employed to determine the toxicity and chemoprofile of Hsp extracts, respectively. Since the detoxified Hsp (dHsp) was defined, its therapeutic effect was evaluated by using an OA rat model induced by monosodium iodoacetate. dHsp at 14 g/kg was orally administered for 28 days, and the pain assessments and histopathological analyses were performed. Real-time PCR (qPCR) was applied to determine the molecular actions of dHsp on cartilage tissue and chondrocytes. MTT assay was conducted to evaluate the effect of dHsp on chondrocytes. Results: The chemoprofile result showed that the contents of toxic alkaloids (aconitine, mesaconitine, and hypaconitine) were decreased but that of non-toxic alkaloids (benzoylaconitine, benzoylmesaconitine, and benzoylhypaconitine) were increased with increasing decoction time. Acute toxicity assay showed that only Hsp with 120 min decoction was non-toxic and can be defined as dHsp. In OA experiment, dHsp significantly attenuated joint pain and prevented articular degeneration from MIA attack. qPCR data showed that dHsp restored the abnormal expressions of Col10, Mmp2, Sox5, Adamts4/5/9, and up-regulated Col2 expression in rat cartilage. In vitro, dHsp-containing serum significantly proliferated rat chondrocytes and regulated the gene expressions of Col2, Mmp1, Adamts9 and Aggrecan in a similar way as the in vivo data. Moreover, aconitine, mesaconitine, and hypaconitine exerted cytotoxic effects on chondrocytes, while benzoylaconitine and benzoylhypaconitine except benzoylmesaconitine exhibited similar molecular actions to dHsp, indicating contributions of benzoylaconitine and benzoylhypaconitine to dHsp. Conclusions: This study defined dHsp and demonstrated dHsp as a potential analgesic and disease modifying agent against OA with molecular actions on the suppression of chondrocyte hypertrophy and extracellular matrix degradation, providing a promising TCM candidate for OA therapy.